The Computer revolution in education : new technologies for distance teaching - Jones, Ann; Scanlon, Eileen; O'Shea, Tim (Brighton, Sussex : Harvester Press , New York : St. Martin's Press, 1987)
This book contains a selection of articles written mostly by staff at the Open University in the United Kingdom about how they have studied and applied the use of computer technology in distance education. Although not stated explicitly by the editors, it appears that the objective of the book is to provide a review of the "state of the art," at least at the time the articles were written. Unfortunately, in spite of the more recent publication date, most of the articles date from the early 1980s. It covers the ways that new information technologies can be applied in education such as microcomputers; mainframes; video-conferencing etc
Includes index.
kjo, 17/01/2019
Loans
Keywords: Distance education - Computer assisted instruction; Information technology; Great Britain